Incidence and survival of cancers among 1, 054 hemophilia patients: A nationwide and 14‐year cohort study. Issue 4 (17th February 2015) - Huang, Yung‐Chieh; Tsan, Yu‐Tse; Chan, Wei‐Cheng; Wang, Jiaan‐Der; Chu, Wei‐Min; Fu, Yun‐Ching; Tong, Kwok‐Man; Lin, Ching‐Heng; Chang, Shin‐Tsu; Hwang, Wen‐Li
Abstract : As life expectancy increases in persons with hemophilia (PWH), more age‐related diseases such as cancer emerge among this patient group. The aim of this study was to investigate incidence and survival of cancers among PWH in Taiwan. We analyzed data of 1, 054 PWH retrieved from Taiwan's National Health Insurance Research Database between 1997 and 2010, by comparing variables to 10540 age‐ and gender‐matched healthy individuals from the general population. There were 43 PWH and 178 individuals of general population with newly diagnosed cancer (RR 2.42, 95% CI 1.74–3.35). The cumulative incidences of cancer in PWH and the general population were 4.7 and 1.9%, respectively. Hepatocellular carcinoma (HCC) was the major type of cancer (17 cases) in PWH; cancer rate was still increased when HCC and HIV‐related cancers were excluded (RR 1.66, 95% CI 1.06–2.59). There was no significant difference observed in lung, colorectal, or prostate cancer occurrence. Compared to the general population, PWH were younger at the time of cancer diagnosis (45.1 vs. 57.2 years old, P value < 0.001), and had fewer co‐morbidities. Nineteen PWH with cancers died during the study period, and no bleeding‐related death was recorded among these patients. The survival rate was not different between PWH and the general population, P  = 0.86. In conclusion, the cumulative incidence of cancer among PWH was higher than the general population. PWH with cancer were younger and had fewer comorbidities, but the survival rates were similar in the two groups.Am. J. Hematol. 90:E55–E59, 2015. © 2015 Wiley Periodicals, Inc.